SISTEM PENJUALAN IKAN HIAS PADA GALERI RAMA DAN RENA BERBASIS WEB - I Wayan Wiranata; Indra Kanedi; Ricky Zulfiandry (Jurnal Media Infotama, 2023)
ABSTRACT : As technology advances today, especially in information systems, the use of computers has become a necessity in the business world and in daily life. The use of information systems for the process of recording sales data that functions to support buying and selling processes, analysis of information systems based on system development data based on promotional activities and sales data of decorative fish gallery, application design systems by adjusting the needs of users based on gallery promotion activities, sales data and results from interviews with the head of decorative fish gallery at Rama dan Rhena Shop, the results of the application design are applied in the design of the sales system application. From the design process to the implementation of the system that has been carried out the sales system of decorative fish gallery at Rama Dan Rhena Shop, the following conclusions can be drawn: a. Sales system of decorative fish gallery at Rama dan Rhena Shop has become a website application that can be accessed flexibly by both users and admins/campus parties, only with an internet connection. b. This sales information system of decorative fish gallery at Rama dan Rhena Shop can be used to record the purchase of stock products at Rama dan Rhena Shop. c. This system can be used to provide purchase transaction reports, sales reports and product reports in detail.